(untitled) (Intent Research Scientific Journal, 2025)
The article examines the direction of rotation of layers along the slope and the placement of working bodies on the plow when plowing slope fields. Diagrams of the rotation of layers on a slope and the location of the working bodies on the plow are presented and the results of one-factor experiments using strain gauge methods are presented, a diagram of the inclination of the palace up and down the slope, and also a diagram of the change in the angle of the unsteady position of the blade depending on the steepness of the slope, the relative position of the body, ripper and spherical disc.